Comparative profitability of agroecological practices in Ethiopian wheat farming - Ng’ang’a, Stanley Karanja; Ogutu, Sylvester Ochieng; Tibebe, Degefie; Akinyi, Devinia; Mockshell, Jonathan (Frontiers in Agronomy, 2025)
IntroductionAgroecology is increasingly promoted as a pathway to sustainable food production, aiming to maximize natural resource use while minimizing external inputs with harmful environmental effects. Agroecological practices can enhance farm productivity while ensuring environmental sustainability. However, these practices often require higher initial investments compared to business-as-usual (BAU) practices, and their profitability and relative risks are not well studied. This research evaluates the profitability and risk of adopting agroecological practices among wheat farmers in Ethiopia.MethodsWe conducted a deterministic cost-benefit analysis (CBA) incorporating sensitivity and scenario analysis to evaluate the profitability and relative risks associated with three agroecological practices: certified wheat seed, optimal site-specific inorganic fertilizer application rates, and drainage of waterlogged soils. The analysis considered yield uncertainty, market price fluctuations, and implementation variability to provide robust insights for decision-making.ResultsThe deterministic CBA revealed that among the three practices, the use of certified seeds was the most profitable, with a net present value (NPV) of US$ 2,531 ha–1. This was followed by optimal site-specific inorganic fertilizer application, with an NPV of US$ 2,371 ha–1. Drainage of waterlogged soils yielded the lowest profitability, with an NPV of US$ 2,099 ha–1.DiscussionThe results indicate that certified seeds and optimal fertilizer rates offer higher financial returns, making them attractive investments for wheat farmers. However, profitability alone does not guarantee adoption. Other factors, including social and behavioral aspects, influence farmer decisions. Future research should integrate these dimensions to develop comprehensive strategies for promoting agroecological practices.ConclusionAdopting agroecological practices has clear economic benefits for Ethiopian wheat farmers, with certified seeds emerging as the most profitable option. These findings provide evidence for stakeholders to design targeted interventions that maximize returns while addressing barriers to adoption.